Parental leave policies and child development: A review of empirical findings - Mathias Huebener (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Parental leave policies are a major policy tool used across OECD countries to support families before and after child birth. There are large differences across countries in the amount and the duration of benefit payments as well as leave entitlement periods. Despite these differences, the shared goal of parental leave policies is to reconcile family life and work, and support child development. While much research attention has been paid to the effects of parental leave policies on maternal labor supply, much less is known about their effects on child development and health. This DIW Roundup summarizes the international literature on parental leave policies and their impact on child outcomes. The literature suggests that the effects are small. However, research in this area is still relatively new and it is too early to draw conclusions about how the design of parental leave policies impacts on child development.
Keywords: 330